Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In electrodynamics, given the vector potential $\vec{A}$, the magnetic field is defined as:
$\vec{B} = \nabla \times \vec{A}$

I'm having trouble figuring out how a coordinate transformation (a rotation) affects these vectors.

If in coordinate system number 1 we have $A_x=x,A_y=0,A_z=0$. Then $\vec{B}=0$.
Now change coordinate systems by rotating.
$x' = \cos(\theta) x - \sin(\theta) y$
$y' = \sin(\theta) x + \cos(\theta) y$
And the inverse is just
$x = \cos(\theta) x' + \sin(\theta) y'$
$y = -\sin(\theta) x' + \cos(\theta) y'$

So $A'_{x'} = \cos(\theta) x,\ A'_{y'} = - \sin(\theta) x,\ A'_{z'} = 0$
$A'_{x'} = \cos(\theta) (\cos(\theta)x' + \sin(\theta)y'),\ A'_{y'} = - \sin(\theta) (\cos(\theta)x' + \sin(\theta)y'),\ A'_{z'} = 0$

But now we have
$B'_{x'}=0,\ B'_{y'}=0,\ B'_{z'}=\frac{\partial}{\partial x'} A'_{y'} - \frac{\partial}{\partial y'} A'_{x'} \neq 0$

A magnetic field shoudn't appear from no-where if I merely rotate my coordinate system. What am I doing wrong? What is the correct way to do these transformations?

share|cite|improve this question
This looks more like something for physics.SE... – J. M. Oct 8 '11 at 13:45
it seems you want to know why $\nabla\times (RA)\ne 0$, where $R$ is a rotation matrix. – Shiyu Oct 8 '11 at 14:41

A magnetic field shoudn't appear from no-where if I merely rotate my coordinate system

That's right, it should not :-)

What am I doing wrong?

It seems to be a simple sign error (or you may have to look up the contravariant transformation law for vectors, e.g. on Wikipedia here). We would like to compute $A(x', y', z')$, so remember that we have to compute, for the first component, $$ A_1(x', y', z') = \frac{\partial x'}{\partial x} * A_1(x, y, z) + \frac{\partial x'}{\partial y} * A_2(x, y, z) + \frac{\partial x'}{\partial z} * A_3(x, y, z) = \frac{\partial x'}{\partial x} * x = x \cos(\theta) $$

and inserting $x = \cos(θ) x'+ \sin(θ) y'$ we get $$ A_1(x', y', z') = \cos(\theta) ( \cos(θ) x'+ \sin(θ) y') $$

and for the second: $$ A_2(x', y', z') = \frac{\partial y'}{\partial x} * A_1(x, y, z) + \frac{\partial y'}{\partial y} * A_2(x, y, z) + \frac{\partial y'}{\partial z} * A_3(x, y, z) = \frac{\partial x'}{\partial x} * x = x \sin(\theta) $$ Inserting again $x = \cos(θ) x'+ \sin(θ) y'$ we get

$$ A_2(x', y', z') = \sin(\theta) ( \cos(θ) x'+ \sin(θ) y') $$ For the z-component of $B$ we now get $$ B_{z'} = \partial_{x'} A_2(x', y' ,z') - \partial_{y'} A_1(x', y' ,z') = \sin(\theta) \cos(\theta) - \sin(\theta) \cos(\theta) = 0 $$ I hope I did not screw up :-)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.